Production of ethanol from sawdust - Borja, Josephine Q. (Animo Repository, 1994)
This study involves the production of ethanol from sawdust (60 mesh) with pyrolysis as a pretreatment process to remove hemicellulose. The solid product after pyrolysis was hydrolyzed to produce fermentable sugars which were fermented to ethanol using Saccharomyces Cerivisiae. A parallel test was conducted using direct acid hydrolysis and results were compared with that of the pyrolysis route. The pyrolysis temperature tested were 260'C and 280'C. Pyrolysis time varied between 1 hour and 1.5 hours for each temperature setting. The solid product of pyrolysis was hydrolyzed using 1 percent H2SO4 and a sawdust of acid ratio of 1:10 (w/v). In the direct acid hydrolysis, hemicellulose was removed by treating the sawdust with 10 percent H2SO4 and the cellulose obtained was decrystallized using 62 percent H2SO4. The decrystallized cellulose was then hydrolyzed using 1 percent H2SO4. The acid hydrolyzate of sawdust pyrolyzed at 260'C for 1.5 hours gave the highest glucose and ethanol yield among the pyrolysis settings. Compared with the direct acid hydrolysis, the pyrolysis route produced a hydrolyzate containing 4.55 percent w glucose against 3.29 percent w in the direct acid hydrolysis. Conversion of cellulose to glucose and glucose to ethanol was 54.12 percent and 42.01 percent in the pyrolysis route and 44.99 percent and 39.83 percent in the direct acid hydrolysis, respectively. The acid hydrolyzates which were fermented to ethanol gave a distillate of 2.54 percent w and 1.35 percent w ethanol in the pyrolysis route and direct acid hydrolysis, respectively. This means a 46.85 percent higher ethanol yield in the pyrolysis route than in the direct acid hydrolysis.